KERENTANAN BENCANA KEBAKARAN DALAM TINJAUAN SOSIAL DAN FISIK DI LINGKUNGAN PAKKOLA KELURAHAN BANGGAE - Syamsiar, Nur Ratika (LPPM Universitas Terbuka, 2024)
This research was conducted in Pakkola Banggae Village. Banggae village is a village that is quite densely populated so that the increasing need for housing and development of dense settlements in Banggae District. This is the main trigger for fire disasters in the Banggae environment, where fires are natural disasters (natural disasters), or disasters caused by human error (man-made disasters). This study aims to determine the level of vulnerability of residential fire disaster in the Pakkola neighborhood of Banggae Village. This study was conducted using qualitative descriptive method and quantitative data analysis using fire hazard index of relevant settlements. According to the findings of the analysis using the residential fire hazard vulnerability index, the Pakkola neighborhood of Banggae Village is included in the high vulnerability class for residential fire hazards.